2015
DOI: 10.1111/1365-2435.12603
|View full text |Cite
|
Sign up to set email alerts
|

Experimental effects of early‐life corticosterone on the hypothalamic–pituitary–adrenal axis and pre‐migratory behaviour in a wild songbird

Abstract: Although laboratory studies have shown that chronic exposure to elevated glucocorticoids during development has profound effects on animals, we still have a poor understanding of the consequences of early-life stress on wild individuals. In an island population of Savannah sparrows (Passerculus sandwichensis), I examined multiple hypotheses to explain how elevated corticosterone exposure during the nestling period influenced both hypothalamic-pituitaryadrenal (HPA) axis function and the subsequent movement and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 98 publications
(223 reference statements)
1
10
0
Order By: Relevance
“…The number of young fledged from a nest was recorded as the number of nestlings banded on the seventh day after hatching. In our analyses, we excluded data for females for which we lacked a complete breeding history (e.g., females for whom we were missing one or more nesting attempts or for which one or more nests was outside the standard study area) or whose nests were the subject of experimental manipulations (e.g., clutch size manipulations; Mitchell et al 2011, Pakkala et al 2015. to the penultimate egg.…”
Section: Definitions Of Reproductive Success Traits and Fitnessmentioning
confidence: 99%
“…The number of young fledged from a nest was recorded as the number of nestlings banded on the seventh day after hatching. In our analyses, we excluded data for females for which we lacked a complete breeding history (e.g., females for whom we were missing one or more nesting attempts or for which one or more nests was outside the standard study area) or whose nests were the subject of experimental manipulations (e.g., clutch size manipulations; Mitchell et al 2011, Pakkala et al 2015. to the penultimate egg.…”
Section: Definitions Of Reproductive Success Traits and Fitnessmentioning
confidence: 99%
“…Although early social experience alters both stress axis programming and social competence, it is as yet unknown whether stress axis programming in early life causally determines the development of social competence, and if so, by which mechanism. Few studies have pharmacologically manipulated the stress axis prenatally or in early life to test for causal links between this axis and behaviour (neophobia [28,29]; aggression [30]; defence against an intruder [31]; migration [32]; predator avoidance [33]; exploration [34]). A well-developed social competence should be particularly important for highly social species, such as cooperative breeders, in which almost all aspects of life include social interactions [4].…”
Section: Introductionmentioning
confidence: 99%
“…This increased maternal provisioning results in nestlings achieving significantly higher size‐adjusted body mass (Bowers, Bowden, et al., ), which could, in theory, influence their stress reactivity. Experimentally increased postnatal corticosterone in nestling Savannah sparrows ( Passerculus sandwichensis ) led to lower stress reactivity than control nestlings (Pakkala, Norris, Sedinger, & Newman, ), so it seems possible that if maternal parental behaviour affects HPA axis function, females could, postnatally, influence stress reactivity of their young. Indeed, in mammals, a number of studies have shown that maternal behaviour can, to some extent, mitigate the effects of any downregulation of the HPA axis in offspring that arises from adversity experienced early in life (Fish et al., ; Weaver et al., ).…”
Section: Discussionmentioning
confidence: 99%